FORMS AND METHODS FOR LABOR INCENTIVE IN MODERN CONDITIONS - Ye. D.Orynbassarova; G.S. Serikova; G.I. Gimranova; M.T. Daniyarova; N.B. Kuttybayeva (Academic Journal of Physical and Chemical Sciences, 2019)
This article proposes the classification of the factors influencing motivation system, which consists of two groups: external (objectively existing and not depending on the company’s management) and internal (generated and dependent on the management of the enterprise); and the influence of these factors in the context of the Republic of Kazakhstan. This study also revealed the basic principles of building effective incentive system and reviewed its types-economic and non-economic. The conclusion about the need for a more flexible approaches to determining the level of basic salary and variable part of the salary, the need to link pay with performance as an employee, and all structural subdivision, and the enterprise as a whole.